Reaching Agents of Change (RAC) Project - International Potato Center (2013)
Through its advocacy efforts since 2011, RAC has generated new investments for promoting orange-fleshed sweetpotato (OFSP) worth 11.4 million USD. RAC has also built institutional capacity to design and implement gender-sensitive projects to ensure wide access and utilization of vitamin A rich OFSP in five selected African countries (Mozambique, Tanzania, Nigeria, Ghana, and Burkina Faso).